1990
DOI: 10.1177/096032719002200401
|View full text |Cite
|
Sign up to set email alerts
|

Illuminance uniformity on desks: Where is the limit?

Abstract: This paper reviews the current uniformity recommendations and shows that they may no longer be appropriate. A study to investigate the acceptable illuminance uniformity across a desk top is described. The illuminance patterns used were representative of those produced by over-spaced luminaires, selective luminaire dimming, e.g. using HF regulation, or lamp failure. Subjects were asked to carry out simulated office tasks and then to rate the various attributes of the lighting and its acceptability. Their task p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 4 publications
1
23
0
Order By: Relevance
“…Slater and Boyce varied the minimum:maximum ratio between 0.2 and 0.8, but found no effect on a variety of paper-based clerical tasks. 36 They noted that this was not unexpected, because calculation based on the Rea and Ouellette relative visual performance model 20 showed that all the illuminance conditions were sufficient to see the tasks. The advent of computers in offices changed the primary task from the horizontal to the vertical plane and raised new research questions about acceptable luminance ratios between the computer screen and paper documents.…”
Section: -31mentioning
confidence: 96%
“…Slater and Boyce varied the minimum:maximum ratio between 0.2 and 0.8, but found no effect on a variety of paper-based clerical tasks. 36 They noted that this was not unexpected, because calculation based on the Rea and Ouellette relative visual performance model 20 showed that all the illuminance conditions were sufficient to see the tasks. The advent of computers in offices changed the primary task from the horizontal to the vertical plane and raised new research questions about acceptable luminance ratios between the computer screen and paper documents.…”
Section: -31mentioning
confidence: 96%
“…As far as threshold values are concerned, a list of some recommended uniformity ratios (table 3) is provided in [90] and reported in [91]. though the entity of such 'compensation' is not quantified.…”
Section: Illuminance Uniformitymentioning
confidence: 99%
“…Slater and Boyce asked participants to rate the evenness of the lighting, its acceptability, and its comfort, in relation to various illuminance ratios across a desktop task (task performance was also measured, but did not vary in relation to uniformity). 90 They concluded that for tasks that are primarily in the center of the desk, illuminance ratios as low as 0.5 would be acceptable for most people. Similarly, rankings of five luminous conditions with several measures of visual comfort were not related to the illuminance uniformity across the desk surface.…”
Section: Affectmentioning
confidence: 99%